The Effect of Learning by Using Computer in The Achievement of the 9th Grade Students in Ajloun Governorate in Physics According to The Lowest Levels of Mental According to Bloom’s Taxonomy - Al- Arood, Khaled Ibrahim Mohammad (Journal of Educational and Psychological Sciences, 2020)
This research aims at knowing the effect of learning by using computer in the achievement of the 9th Grade students in physics according to the lowest levels of mental according to (bloom) Taxonomy, To achieve this aim, the research use the Semi- experimental approach design to study the effect of the independent variable (computerized program for physics- 9th Grade) on the dependent variable which represents the achievement of the three lower level of Bloom’s Taxonomy (knowledge, understanding, application). Two equal groups were designed, one is experimental and the other is controlled. Each one consists of 30 students, and both are tested randomly. The first group is taught wing the physics curriculum for 9th Grade using the computer as it is the experimental group. The second group is trained on the same material by using the conventional method which emphasizes the practical use of lab as it is the controlled group. Both groups undergo pre and posttests with the same subjects of the curriculum, The results of the pretest indicate that there are statistical differences, which assert that both groups are equal The researcher also indicates that there is an extreme relationship between using the computer and high level of achievement that is represented in (understanding and application) there is necessity to use the computer in teaching physics, to connect the computer with all subject and to regal it as an essential access in designing the curriculum of all subject, so as to enable the teacher and the student to use it with high qualification in teaching and learning all the stages, In addition there is an the use of educational programs that are linked with the standard curricula and with all the subjects, and the attend to increase the computerized education among teachers and students by increasing teacher courses and adding new skills to computer subject for students, and increasing cooperation between Ministry of Education and specialized companies or organizations in designing computerized programs.